2021
DOI: 10.1245/s10434-021-09946-4
|View full text |Cite
|
Sign up to set email alerts
|

Management of Soft Tissue Sarcomas in Extremities: Variation in Treatment Recommendations and Surveillance According to Specialty and Continent

Abstract: Background This study aimed to provide an insight into clinical decision-making and surveillance strategy of sarcoma specialists for patients with primary soft tissue sarcoma of the extremities (eSTS). The secondary aim was to quantify the role of patient- and tumor-specific factors in the perioperative management. Methods Members of sarcoma societies were sent a Web-based 21-item survey about eSTS management. The survey concerned only primary resectable h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
(43 reference statements)
1
9
0
Order By: Relevance
“…[33][34][35] These patients were identified using prediction tools, which anticipate individual risks of metastasis formation and death based on characteristics of the patient, tumour, and treatment. 36,37 A survey among sarcoma specialists reported that 81% consider the use of a prediction tool for the indication of (neo)adjuvant chemotherapy in patients with a primary eSTS, 12 marking a recent trend to a more patient-tailored approach in the management of these tumours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[33][34][35] These patients were identified using prediction tools, which anticipate individual risks of metastasis formation and death based on characteristics of the patient, tumour, and treatment. 36,37 A survey among sarcoma specialists reported that 81% consider the use of a prediction tool for the indication of (neo)adjuvant chemotherapy in patients with a primary eSTS, 12 marking a recent trend to a more patient-tailored approach in the management of these tumours.…”
Section: Introductionmentioning
confidence: 99%
“…7,8,38 Prediction tools in the form of a nomogram or a computeror smartphone-based calculator are commonly used to estimate oncological events such as the risk of recurrence and death. 12,39 These tools generate individual probabilities of an event based on a combination of factors accounting for the fact that patients have many characteristics that may vary simultaneously. This results in the identification of a more accurate individual prognosis, which is easier to explain compared with conventional staging systems in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Our cross-sectional study aimed to acquire insight into the variation of eSTS management across the world and to assess the importance of several clinicopathologic risk factors for the indication of multimodality therapy. 3 Although studies have shown better patient outcomes when adhering to the clinical guidelines, this study showed remarkable variation in eSTS management and surveillance across continents and physician specialties. Notably, a wide variation in attitude towards perioperative CTX was found across specialties.…”
Section: Presentmentioning
confidence: 70%
“…Recently, improvements in detection through more sensitive molecular techniques and imaging technologies (e.g. PET), as well as in standardized coding systems have increased STS diagnosis and certification, to a greater extent in areas characterized by high-quality health systems (Toro et al , 2006; Pasquali et al , 2019). These advancements can partly justify the higher mortality rates in some high-income regions of North America and Western Europe (Gage et al , 2019).…”
Section: Discussionmentioning
confidence: 99%